Understanding your body matters: Effects of an entertainment-education serial radio drama on fertility awareness in Rwanda. Issue 8 (3rd August 2018) - Shelus, Victoria; VanEnk, Lauren; Giuffrida, Monica; Jansen, Stefan; Connolly, Scott; Mukabatsinda, Marie; Jah, Fatou; Ndahindwa, Vedasta; Shattuck, Dominick
Abstract : Given widespread misunderstanding of pregnancy risk, awareness of one's fertility has the potential to influence sexual and reproductive health behaviors. This mixed-methods study examined the impact of a serial radio drama in Rwanda, Impano n'Impamba, on fertility awareness and other factors related to family planning uptake by comparing listeners and non-listeners in a nationally representative household survey ( n = 1477) and analyzing in-depth interviews with 32 listeners. Listeners had higher fertility awareness than non-listeners for key concepts, including the menstrual cycle, onset of fertility, and postpartum pregnancy risk. Qualitative interviews suggest discussion groups provided an invaluable opportunity to ask questions to a knowledgeable facilitator and clarify the fertility awareness information. No significant differences in modern family planning use or intention to use were found between listeners and non-listeners, but listeners reported greater supportive norms, self-efficacy, and discussion of family planning. Qualitative interviews suggest that increased discussion about family planning occurred because the drama emboldened people to talk about uncomfortable and taboo topics. Post-broadcast, listeners of Impano n'Impamba had greater fertility awareness then non-listeners and were more likely to experience intermediate outcomes related to family planning such as perception of positive family planning norms, a feeling of self-efficacy, and increased communication with others related to family planning. The study provides lessons for future interventions with the aim of increasing fertility awareness to improve sexual and reproductive health.